Prognostic value of sST2 in patients with heart failure with reduced, mid-range and preserved ejection fraction. (1st April 2020) - Song, Yu; Li, Fuhai; Xu, Yamei; Liu, Yuan; Wang, Yanyan; Han, Xueting; Fan, Yuyuan; Cao, Juan; Luo, Jie; Sun, Aijun; Hu, Kai; Zhou, Jingmin; et al.
Abstract: Backgrounds: Prognostic value of soluble suppression of tumorigenecity (sST2), a novel circulating biomarker for myocardial fibrosis, remains elusive in the heart failure patients with preserved ejection fraction (HFpEF). Methods: 405 consecutive patients with heart failure (HF) were enrolled prospectively, and were grouped into HF with reduced ejection fraction (HFrEF, N  = 215), HF with mid-range ejection fraction (HFmrEF, N  = 80) and HFpEF ( N  = 110). The primary endpoint was the composite endpoint of all-cause death and HF rehospitalization. Results: After a median of 12 months, 139 patients reached the primary endpoint, with 57 patients died and 82 patients rehospitalized. Multivariate analysis confirmed that sST2 was an independent risk factor of the primary endpoint for all HF patients [hazard ratio (HR) 2.35, 95% confidence interval (CI) 1.30–4.22, P  = 0.004]. Predicting efficacy of sST2 on outcomes was higher for HFpEF (HR 6.48, 95%CI 1.89–22.21, P  = 0.003) as compared to HFrEF (HR 3.21, 95% CI 1.67–6.19, P  = 0.000). But the association between sST2 and outcomes in HFmrEF is not statistical (HR 3.38, 95%CI 0.82–13.86, P  = 0.091). The combined use of sST2 and N terminal pro B type natriuretic peptide (NT-proBNP) could improve the prognostic value compared to using NT-proBNP alone in HFrEF (AUC = 0.794 vs. 0.752, P  = 0.034). Conclusion: Higher baseline sST2 levels are associated with increased risk of all-cause death and HF rehospitalization in patients with HF independent of ejection fraction. The combined use of sST2 and NT-proBNP could improve the prognostic value than using these two values alone, especially for HFrEF patients. Highlights: Serum sST2 levels were similar among HFrEF, HFmrEF and HFpEF patients. sST2 remained as the independent risk factor of the adverse outcomes. Predicting efficacy of sST2 on outcomes was higher for HFpEF as compared to HFrEF. The combined use of sST2 and NT-proBNP could improve the prognostic value in HFrEF.